PENGAWETAN LIMA JENIS KAYU MENURUT METODE RENDAMAN PANAS-DINGIN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1988)
The  degree  of  protection  offerd   by a wood  preservative  depends  upon  the  quality  of preservative retained by the timber, the depth penetration, and  the permanence of  preservative   in  the wood.On  the hot and  cold  bath process,  the  timber is immersed in cold preservative  and  the  bath and timber are heated up together to around 70°C for one, two, three hours until  the timber  is hot  throught,  and  the whole  then allowed to cool down for 24  hours.For  all  timber species tested   in  this  experiment   the  depth   of  penetration  and  retention    of  preservative  was measured  after  treatment.  The  result  of  which  can be seen in Table 1.  After  calculated  and analysis (Table 2 and Table  3) the following conclusions  could  be draw :Timber species  has highly  significant  on  boron penetration  and retention.  Boron penetration   a seemed  to  be generally getting  deeper  with  increased   hot  soaking  hours; but one hour  is fully.Generally  speaking, hot  and cold  bath process  are  to  be preferred  although   with  mahoni  (Swietenia  mahogani  Jack:) and  tanjung  (Mimmusops  elengi   L.)  timbers  the preservative   retention less than  the  other  timbers.